Seasonal Differences in the Attenuation of Polar Trace Organics in the Hyporheic Zone of an Urban Stream. Issue 1 (20th January 2022) - Mueller, Birgit M.; Schulz, Hanna; Höhne, Anja; Putschew, Anke; Lewandowski, Joerg
Abstract: Attenuation of trace organic compounds (TrOCs) in a river occurs to a large extent in its hyporheic zone. A major part of the attenuation of polar TrOCs is of microbial origin. As microbial activity depends on temperature and redox conditions, seasonal differences in TrOC attenuation are likely. We investigated TrOC attenuation at a river influenced by treated wastewater during two sampling campaigns, one in summer and one in winter. In addition to redox conditions and temperature, we also determined residence times of porewater in sediment using three methods: (a) non‐parametric deconvolution of electrical conductivity time series, (b) the model VFLUX 2.0 based on temperature time series (only summer), and (c) applying Darcy's law to differences in hydraulic heads (only summer). Contrary to our expectations, we found higher attenuation for 12 out of 18 TrOCs in winter, while three TrOCs were better attenuated in summer. Sediment conditions varied between seasons as more of the top sandy layer with a higher hydraulic permeability accumulated on the river bed in summer. As a result, residence times in the sediment were shorter in summer. In winter, longer residence times, lower temperatures, and a steeper oxygen gradient in sediment coincided with higher TrOC attenuation. Further research is needed to understand our unexpected findings and underlying mechanisms. Key Points: The attenuation of 12 out of 18 trace organic compounds (TrOCs) in the hyporheic zone was higher in winter while three TrOCs were attenuated better in summer Residence times in sediment were longer and more diverse in winter The extent of the oxic sediment was similar between seasons but the gradient from the oxic to anoxic zone was steeper in winter